Lynd Ward's wordless novels, 1929-1937 visual narrative, cultural politics, homoeroticism - Scott, Grant F. (New York, NY : Routledge, 2022)
This book offers the first multidisciplinary analysis of the "wordless novels" of American woodcut artist and illustrator Lynd Ward (1905-1985), who has been enormously influential in the development of the contemporary graphic novel. The study examines his six pictorial novels, each part of an evolving experiment in a new form of visual narrative that offers a keen intervention in the cultural and sexual politics of the 1930s. The novels form a discrete group - much like Beethoven's piano sonatas or Keats's great odes - in which Ward evolves a unique modernist style (cinematic, expressionist, futurist, realist, documentary) and grapples with significant cultural and political ideas in a moment when the American experiment and capitalism itself hung in the balance. In testing the limits of a new narrative form, Ward's novels require a versatile critical framework as sensitive to German Expressionism and Weimar cinema as to labor politics and the new energies of proletarian homosexuality.
Keywords: LITERARY CRITICISM / Gay & Lesbian; LITERARY CRITICISM / American / General; Ward, Lynd, -- 1905-1985 -- Criticism and interpretation; Stories without words -- History and criticism